PENENTUAN TINGKAT KERAWANAN LONGSOR MENGGUNAKAN METODE FUZZY LOGIC - Akshsr Akshar (Teknik Informatika Universitas Malikussaleh, 2013)
Landslides is one form of natural disasters that often occur suddenly, its effects cause substantial losses in terms of both material and loss of life. In Indonesia, natural disasters are very common one is because Indonesia has a high rainfall which category each year. The authorities deal with this natural disaster is very difficult to predict when the occurrence of landslides in certain areas because the symptoms are not seen clearly coupled with the location of areas difficult to reach. In the theory of fuzzy logic could be worth a value of true and false at the same time but how much truth and error a value depending on how much weight they have membership. Fuzzy logic contained in the fuzzy set is groupings of things based on variable language (linguistic variables)are expressed in the membership function of zero to one. Fuzzy logic-based intelligent systems can be used as an examination to predict areas prone to landslides. In this research, the landslide prediction system created a web-based reference that can be used as a tool to predicting certain areas against possible landslides. Users must input some parameters consisting of rainfall, soil slope, elevation of the land, soil type, and land use which is subsequently processed into the system by using fuzzy logic and the results will be displayed according to the input data that has been entered by the user. It can be concluded that the landslide-prone area prediction system has high accuracy and can beused easily.